GENOTYPIC ADAPTABILITY FOR SEED YIELD AND PHYSIOLOGICAL TRAITS IN SESAME (SESAMUM INDICUM L.) - KUMAR, NARENDRA; S. B. S. TIKKA; M. C. DAGLA; RAM, BHAGIRATH; H. P. MEENA (The Bioscan, 2013)
A study was carried out using thirty six sesame genotypes under four environments to assess the genotype × environment interaction and their stability across the environments for seed yield and physiological traits. The pooled analysis of variance due to genotypes, environments as well as genotype × environment interactions were highly significant for all the characters except for photosynthetic rate at 40 days after sowing (DAS) for genotypes, environments and genotype × environment interaction. Genotype × environment (linear) variance component was more than that of pooled deviations for mostly characters including seed yield. Grain yield per plant had significant positive correlation with harvest index (0.82) and leaf area index at 60 DAS (0.32) at low fertility condition, whereas it was also positive and highly significant with harvest index (0.55), leaf area index at 60 DAS (0.58) and photosynthetic rate at 60 DAS (0.44) at high fertility condition. It indicated that these physiological traits had greater magnitude of correlation with seed yield under high input conditions irrespective of timely and late sown environments. Therefore, selection under high fertility conditions leads to genetic improvement of physiological traits.